Structural and nanostructural behavior of deuterium implanted Highly Ordered Pyrolytic Graphite investigated by combined High Resolution Transmission Electron Microscopy, Scanning Electron Microscopy and Raman microspectrometry. (November 2015) - Le Guillou, M.; Rouzaud, J.N.; Deldicque, D.; Toulhoat, N.; Pipon, Y.; Moncoffre, N.
Abstract: This work aims at studying the impact of D + ion implantation and thermal annealing on the organization of Highly Ordered Pyrolytic Graphite (HOPG). Raman microspectrometry, High Resolution Transmission Electron Microscopy (HRTEM) and Scanning Electron Microscopy (SEM) were used to characterize the multiscale organization of HOPG. For the first time, HRTEM images were processed, allowing a better estimation of structural parameters such as size of the graphene layers, mean interlayer spacing, distribution of the relative orientations of the graphene layers, defined as the spatial orientation of the stacked layers. Ion implantation induces a strong disordering of the HOPG reflected by a decrease of the length of graphene layers, and an increase of both angular dispersion and interlayer distance and a significant decrease of the Basic Structural Unit (BSU) diameter. Thermal annealing up to 1000 °C leads to partial reordering of the HOPG, with increase of the mean length of the graphene layers, decrease of their angular dispersion and interlayer distance and larger and increasingly parallel oriented BSUs. Even if the conservation of the lamellar nanostructure favors reordering, the latter is only partial since annealing temperature is far from 2000 °C, temperature above which stiff and perfect layers may be obtained.